Characteristics of Math national-standardized school exam test items in junior high school: What must be considered? - Argianti, Atin; Retnawati, Heri (Graduate School, Universitas Negeri Yogyakarta, 2020)
This research aims to determine the characteristics of items for the Math National Standardized School Exam (NSSE) in Junior High School (JHS) in grade 9. This study is descriptive-explorative quantitative research. The samples chosen were 293 ninth-grade students’ answers at state JHS of 3 Pati with a package of questions consisting of 30 items. The data collected is an NSSE test instrument and participants’ answers at State JHS of 3 Pati 2018/2019, collected by documentation. Experts validated the NSSE instrument, and the characteristic items of the NSSE instrument were analyzed using the classical test theory approach using Quest program. The question items of the math NSSE test at state JHS of 3 Pati are generally moderately good. Based on the classical theory approach, the result of instrument validity from expert judgment was 0.924, while the validity of items was 17 (56.7%) of items were very valid. The reliability was 0.78 (reliable category). Generally, Math NSSE items are in the easy category with a percentage of 83.3%. The discrimination index results indicate that, in general, the NSSE items are in a moderate category with a percentage of 60% (18 items). The distraction effectiveness shows that NSSE items are in the functional category with a percentage of 50%.